Pelatihan Evaluasi Pembelajaran Interaktif Berbasis Gamifikasi Menggunaan Quizizz Pada Bimbingan Belajar Al Hikmah Palembang - Abdul Basyith; Fitriya Fauzi (Jurnal Nasional Pengabdian Masyarakat, 2021)
The impact of the rapid development of information technology, especially in the field of education, has provided additional media in the teaching and learning process, both in teaching media and in learning evaluation. Through gamification techniques can make learning more fun and innovative. However, many teachers have still not been able to use the information technology-based media. From the preliminary survey conducted by this service team of 10 Al-Hikmah Tutoring teachers, it was seen that only 1 teaching staff or 10 percent knew of gamification-based learning media in the form of Quizizz. The implementation team succeeded in carrying out service activities aimed at all Al-Hikmah Tutoring educators for 2 days. Of the 10 teachers who participated in the training process using Quizizz, it was found that from the evaluation of the implementation of this service, it was found that 100% of the teachers were able to operate the Quizizz learning media. As many as 100 percent understood the existing features, and 100 percent also wanted to use Quizizz media as a tool for learning evaluation media. In addition, students also expect teachers to use this Quizizz in every learning evaluation activity